Targeting Tumor Microenvironment by Small-Molecule Inhibitors - Zhong, Shangwei (Transl Oncol, 2019)
The tumor microenvironment (TME) is a hypoxic, acidic, and immune/inflammatory cell–enriched milieu that plays crucial roles in tumor development, growth, progression, and therapy resistance. Targeting TME is an attractive strategy for the treatment of solid tumors. Conventional cancer chemotherapies are mostly designed to directly kill cancer cells, and the effectiveness is always compromised by their penetration and accessibility to cancer cells. Small-molecule inhibitors, which exhibit good penetration and accessibility, are widely studied, and many of them have been successfully applied in clinics for cancer treatment. As TME is more penetrable and accessible than tumor cells, a lot of efforts have recently been made to generate small-molecule inhibitors that specifically target TME or the components of TME or develop special drug-delivery systems that release the cytotoxic drugs specifically in TME. In this review, we briefly summarize the recent advances of small-molecule inhibitors that target TME for the tumor treatment.